Prophage Gene Rv2650c Enhances Intracellular Survival of Mycobacterium smegmatis - Fan, Xiangyu; Liu, Zichen; Wan, Zhibin; Zou, Hanlu; Ji, Mengzhi; Sun, Kaili; Gao, Rongfeng; Li, Zhongfang; Li, Wu (Frontiers in Microbiology, 2022)
Background: Induced by the pathogen Mycobacterium tuberculosis, tuberculosis remains one of the most dangerous infectious diseases in the world. As a special virus, prophage is domesticated by its host and are major contributors to virulence factors for bacterial pathogenicity. The function of prophages and their genes in M. tuberculosis is still unknown. Methods: Rv2650 is a prophage gene in M. tuberculosis genome. We constructed recombinant M. smegmatis to observe bacteria morphology and analyze the resistance to various adverse environments. Recombinant and control strains were used to infect macrophages, respectively. Furthermore, we performed ELISA experiments of infected macrophages. Results: Rv2650c affected the spread of colonies of M. smegmatis and enhanced the resistance of M. smegmatis to macrophages and various stress agents such as acid, oxidative stress, and surfactant. ELISA experiments revealed that the Rv2650c can inhibit the expression of inflammatory factors TNF-α, IL-10, IL-1β, and IL-6. Conclusions: This study demonstrates that the prophage gene Rv2650c can inhibit the spread of colonies and the expression of inflammatory factors and promote intracellular survival of M. smegmatis. These results build the foundation for the discovery of virulence factors of M. tuberculosis, and provide novel insights into the function of the prophage in Mycobacterium.